Increasing Public Awareness in Environmental Preservation in the City of Binjai - Dewi, Dahlia Kusuma; Siregar, Dahris; Mahasari, Jamaluddin; Syahrin, Alvi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The lack of public awareness of the environment is a problem that is still sustainable today, due to lack of knowledge and still low public awareness to love the environment, especially in terms of greening, as evidenced by the increasing number of buildings without re-greening. so that concern for the environment itself is minimal. The movement of 500 trees or flower plants and forest plants, and carried out legal counseling activities on environmental conservation in Binjai City, aims to realize awareness of the people of Binjai City in maintaining environmental sustainability through understanding the paradigm of environmental protection and management as regulated in Law No. 32 of 2009 concerning Environmental Protection and Management. This legal counseling uses a statutory approach by first examining laws related to environmental conservation which aims at sustainable development. The paradigm of environmental conservation with the 3R system is Reuse (Reusing waste that can still be used or can function other), Reduce (Reduce everything that causes or causes waste), Recycle (Reprocessing waste or recycling into a product or item that can be useful), becomes a solution to maintain environmental sustainability.